Interactive Digital Media Based on Ispring Suite 11 to Improve Science Literacy of Elementary School Students - Pinasti, Rahma; Pratiwi Kartika Sari (Universitas Pendidikan Ganesha, 2025)
There are still a few engaging and interactive digital media to help students improve their scientific literacy and address students' low understanding of basic scientific concepts. This study aims to develop interactive digital media based on the iSpring Suite 11 to improve students' scientific literacy in Natural Sciences (IPAS) learning in grade IV of elementary school. The interactive learning media developed in this study presents IPAS material with multimedia features such as audio, quizzes, animations, and simulations. This type of research uses the Research and Development (R&D) method with the Hannafin & Peck development model (Needs assessment, Design stage, Development and Implementation). The three phases are connected to evaluation and revision activities. The validation results of material experts are 94%, language experts 80% and media experts 95% with a very valid category. The effectiveness test of the learning device shows high results, namely 92% for small group trials and 96% for large group trials. The results of the pretest and posttest showed a statistically significant increase in scientific literacy, based on the normality test (significance value > 0.05) and the T test (significance value < 0.05). The conclusion of this study, innovative and interactive digital media based on Ispring Suite 11, is valid, practical, and effective for improving the scientific literacy of elementary school students is an alternative solution for innovative, interactive media and supports the learning needs of the 21st century. Further research recommendations are developing learning media based on Ispring Suite 11 by exploring new features for students at the next level.